Volcanic emissions, aerosol processes, and climatic effects - Schmidt, Anja; Carn, Simon (Digital Commons @ Michigan Tech, 2022)
This chapter describes how volcanic emissions into the troposphere and stratosphere affect aerosol properties, radiation, and climate. It begins by describing aerosol and precursor gas emissions from passive degassing and volcanic eruptions, including a time history of emissions over the satellite era since 1978. It describes how records of volcanism and volcanic effects on climate can be reconstructed from ice cores, tree rings, and written historical records. It then describes how volcanic emissions affect aerosol physical and optical properties and how these alter atmospheric radiation and global temperature. The chapter concludes by outlining the status of models and the challenges in using them to quantitatively link volcanic sulfate deposition records in ice cores to their climatic effects.